Does Hemoglobin mass increase with several years of endurance training? - Controlled cross-sectional study with 16, 21 and 28 years old elite XC-skiers and triathletes - Steiner, T.; Boutellier, U.; Wehrlin, J. P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Recent research results (Prommer et al. 2008) put into question, whether haemoglobin mass (HbM) - an important limiting factor of VO2max - unlike as guessed so far (Sawka et al. 2000) can be increased in endurance athletes with endurance training. Little is known about the effects of long lasting endurance training on HbM in adolescents. The aim of this controlled cross-sectional study was to evaluate if there are differences in HbM between endurance athletes at the age of 16 years, 20-23 years and older than 23 years. Methods: In three endurance athlete groups at different age (AG16: 15.9±0.7 years, n=15, national top 15 ranking in XC-skiing and triathlon in 2008, no national team at this age; AG21: 21.3±0.9 years, n=14 and AG28: 27.5±3.0 years, n=16 from the national teams in XCskiing and triathlon) as well as in three age matched control groups (< 2h endurance training per week; KG16: 15.9±0.3 years, n=16; KG21: 21.3±1.2 years, n=15; KG28: 28.1±4.0 years, n=16) we measured, among others, HbM (CO-rebreathing) and VO2max. Results: In AG16 HbM (12.3 ±0.8 g/kg) as well as VO2max (66.1 ±3.6 ml/min/kg) was lower (p<0.01) than in AG21 (14.2 ±1.1 g/kg / 72.9 ±3.6 ml/min/kg) and AG28 (14.6 ±1.1 g/kg / 73.4±6.0 ml/min/kg), while there were no differences between AG21 and AG28 and among the control groups. Between AG16 and KG16 (12.0 ±1.0 g/kg / 58.9±5.0 ml/min/kg) only VO2max was different (p<0.001) but not HbM (p=0.39). In the AG21 and AG28 groups HbM and VO2max were higher (p<0.001) than in the matchable control groups (KG21: 12.5 ±1.0 g/kg / 57.5 ±6.6 ml/min/kg. KG28: 12.1 ±1.0 g/kg / 54.7 ±6.2 ml/min/kg). Discussion: Our results indicate that HbM increases between the age of 16 and 21 in elite endurance athletes, but not between 21 and 28 years. Endurance training of adolescents seems to influence VO2max much more than HbM. That HbM doesn`t change in older athletes we confirmed in another study (Wehrlin & Clénin, 2009), where we even didn`t find a difference in HbM between U18, U23 and elite cyclists. Wherefore, HbM might have its biggest potential for development between the age of 16 and 18 in endurance athletes. When interpreting our data, we have to take into account that cross-sectional designs implicate always possible selection bias, although the selection guidelines for the athletes at the age of 16 have been clearly defined (top 15 ranking). However, data in adolescents from longitudinal studies are needed to verify our findings. Conclusion: Our data suggest that with several years of endurance training HbM increases between the age of 16 to 21 years but not between the age of 21 to 28 years in endurance athletes.